Paradigm and Socio-Historical Context of Islamic Sciences in an Epistemological Study - Nur Isra' Ahmad; Ushwa Dwi Masrurah Arifin Bando (MADINAH, 2026)
This research aims to identify the theories that shape the paradigm of Islamic sciences, trace their relationship to socio-historical contexts, and develop a new epistemological framework that is relevant to contemporary studies. The method used is a literature review with content analysis of relevant literature. The results of the study show that Islamic sciences are based on revelation as a normative basis, but develop through reason and empirical experience so as to form a historical construction that is open to critical study. The deductive paradigm maintains the consistency of religious teachings, while the inductive paradigm is born from the practical needs of the community through observation and experimentation. Both interact with revelation, rationality, and social reality, giving birth to a comprehensive, rational, and empirical epistemology of Islam. The novelty of this research lies in the integrative perspective that connects deduction-induction with socio-historical reality. Therefore, further research needs to be directed to empirical studies in the fields of education, technology, and public policy, as well as to expand dialogue with contemporary science so that Islam's contribution to the global scientific tradition is more real.